1979
DOI: 10.1038/hdy.1979.5
|View full text |Cite
|
Sign up to set email alerts
|

Herbivorous insects colonising cyanogenic and acyanogenic Trifolium repens

Abstract: SUMMARYInsect herbivores colonizing cyanogenic and acyanogenic white clover plants were investigated. With the exception of aphids, the herbivores studied were infrequent visitors and failed to discriminate between the two phenotypes. Aphids, however, were two to three times more abundant on acyanogenic than cyanogenic plants. Evidence of visible insect feeding damage was identical for both phenotypes. The evidence suggests that the trait of cyanogenesis confers protection against herbivory by aphids and, poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…Most recent investigations of the cyanogenesis polymorphism in white clover have focussed on the selective factors themselves. There is conclusive evidence that herbivory by slugs and snails, and perhaps aphids, selects against the acyanogenic phenotype (Angseesing, 1974;Angseesing and Angseesing, 1973;Crawford-Sidebotham, 1972;Dirzo and Harper, 1982a;Dritschilo et al, 1979;Horrill and Richards, 1986;Jones, 1962Jones, , 1966.…”
Section: Resultsmentioning
confidence: 99%
“…Most recent investigations of the cyanogenesis polymorphism in white clover have focussed on the selective factors themselves. There is conclusive evidence that herbivory by slugs and snails, and perhaps aphids, selects against the acyanogenic phenotype (Angseesing, 1974;Angseesing and Angseesing, 1973;Crawford-Sidebotham, 1972;Dirzo and Harper, 1982a;Dritschilo et al, 1979;Horrill and Richards, 1986;Jones, 1962Jones, , 1966.…”
Section: Resultsmentioning
confidence: 99%
“…In many studies, cyanogenesis has been found to be an effective deterrent against generalist clover herbivores, including slugs and snails (for example, see Angseesing, 1974;Dirzo and Harper, 1982a, b;Kakes, 1989), insects (Dritschilo et al, 1979;Pederson and Brink, 1998) and small mammals (Saucy et al, 1999;Viette et al, 2000). These findings suggest that cyanogenesis is adaptive in the presence of herbivores.…”
Section: Agents and Targets Of Selection In Clover Cyanogenesis Clinesmentioning
confidence: 99%
“…They attributed this differential mortality to selection by slugs of Huia seedlings, which are strongly cyanogenic, in preference to Tahora seedlings, which are less cyanogenic (Williams et al 1982). However, available data indicate that small herbivores preferentially eat acyanogenic phenotypes (Crawford-Sidebotham 1972;Angseesing 1974;Dritschilo et al 1979;Ennos 1981) though the evidence is equivocal (Bishop & Korn 1969;Miller et al 1975). There was no indication of differential feeding by invertebrate pests in this trial, despite a wide range in cyanogenic potentials of the cultivars used (D. F. Chapman unpublished data).…”
Section: Seasonal Differencesmentioning
confidence: 87%